The impact of illegal immigration and human trafficking on Arab national security - Karrar, Ebtihal Gamal El-Deen El-Sadeg (Journal of Economic, Administrative and Legal Sciences, 2022)
This study investigated the phenomenon of illegal immigration and human trafficking in the Arab countries and its impact on Arab national security. The study adopted the descriptive analytical approach and the historical approach to test the validity of the hypotheses. It identified that there are political, security and economic reasons behind this phenomenon. The political reasons were the tyranny of the political regimes and conflicts and wars going on in these countries. It is found that illegal immigration augments human trafficking, and negatively affects Arab national security such that the exploitation of immigrants by terrorist movements in wars and as a source of finance and laundering crimes. Furthermore; there are health threats represented in the transmission of infectious diseases. The study recommended the necessity of cooperation of all Arab countries to combat illegal immigration and human trafficking, and directing resources to combat illegal immigration, supporting and encouraging young people to set up projects to achieve their aspirations, the need to introduce democracy and the commitment to good governance, transparency, freedoms and fighting corruption.